De Novo proteome analysis of genetically modified tumor cells by a metabolic labeling/azide-alkyne cycloaddition approach - Ballikaya, Seda; Lee, Jennifer; Warnken, Uwe; Schnölzer, Martina; Gebert, Johannes; Kopitz, Jürgen (Molecular & cellular proteomics, 2014)
Activin receptor type II (ACVR2) is a member of the transforming growth factor type II receptor family and controls cell growth and differentiation, thereby acting as a tumor suppressor. ACVR2 inactivation is known to drive colorectal tumorigenesis. We used an ACVR2-deficient microsatellite unstable colon cancer cell line (HCT116) to set up a novel experimental design for comprehensive analysis of proteomic changes associated with such functional loss of a tumor suppressor. To this end we combined two existing technologies. First, the ACVR2 gene was reconstituted in an ACVR2-deficient colorectal cancer (CRC) cell line by means of recombinase-mediated cassette exchange, resulting in the generation of an inducible expression system that allowed the regulation of ACVR2 gene expression in a doxycycline-dependent manner. Functional expression in the induced cells was explicitly proven. Second, we used the methionine analog azidohomoalanine for metabolic labeling of newly synthesized proteins in our cell line model. Labeled proteins were tagged with biotin via a Click-iT chemistry approach enabling specific extraction of labeled proteins by streptavidin-coated beads. Tryptic on-bead digestion of captured proteins and subsequent ultra-high-performance LC coupled to LTQ Orbitrap XL mass spectrometry identified 513 proteins, with 25 of them differentially expressed between ACVR2-deficient and -proficient cells. Among these, several candidates that had already been linked to colorectal cancer or were known to play a key role in cell growth or apoptosis control were identified, proving the utility of the presented experimental approach. In principle, this strategy can be adapted to analyze any gene of interest and its effect on the cellular de novo proteome.